Girls’ Self-Esteem and its Association with Self-Stigma toward Obesity - Mohammed Baqer Abbas Al-Jubouri; Hassan A. Athbi; Wuod A. Hassan; Hanan H. Owed; Nabaa S. Malik; Hadeel B. Jasim; Maha M. Sabar; Fatimah A. Almusaedi; Namaa D. Salman (Iranian Journal of Nursing and Midwifery Research)
Background: Obesity among girls can lead to physical, psychological, or social problems. Enhancing self-esteem and reducing self-stigma toward obesity can play a crucial role in girls’ health. This study aims to assess girls’ self-esteem and its association with self-stigma toward obesity. Materials and Methods: A descriptive cross-sectional design was used to meet the study’s objective. A convenience sampling method was used to gather the sample from 24 middle and high schools in five cities across Iraq from (January 2023 to March 2023). A total of 1326 girls participated in the study. Weight Self-Stigma Questionnaire and Rosenberg Self-Esteem Scale were used to assess self-stigma and self-esteem regarding obesity. Pearson’s rho (r) and one-way ANOVA were used to analyze the data by SPSS version 26. Results: In total, 1200 girls scored on weight self-stigma and self-esteem, and the means (SD) were 29.28 (±7.06) and 30.47 (4.43), respectively. The results revealed that there was a significant negative correlation between weight self-stigma and self-esteem (r = -.404, p < 0.001). Conclusions: Iraqi girls with higher obesity-related stigma have lower self-esteem. Hence, as obesity can affect girls’ body image, increasing girls’ self-esteem can reduce their weight self-stigma.